Neuroprotective effect of naringin against cerebellar changes in Alzheimer’s disease through modulation of autophagy, oxidative stress and tau expression: An experimental study - Hassan, Hend M.; Elnagar, Mohamed R.; Abdelrazik, Eman; Mahdi, Mohamed R.; Hamza, Eman; Elattar, Eman M.; ElNashar, Eman Mohamed; Alghamdi, Mansour Abdullah; Al-Qahtani, Zainah; Al-Khater, Khulood Mohammed; Aldahhan, Rashid A.; ELdesoqui, Mamdouh (Frontiers in Neuroanatomy, 2022)
Alzheimer’s disease (AD) is a neurodegenerative disorder characterized by gradual cognitive decline. Strong antioxidants that inhibit free radicals, such as polyphenols, reduce the likelihood of developing oxidative stress-related degenerative diseases such as AD. Naringin, a flavonoid found in citrus fruit shown to be neuroprotective, reduce oxidative damage and minimize histopathological changes caused by ischemic reperfusion, enhance the long-term memory in AD animal models. This work aimed to comprehend the role of naringin in the defense of the cerebellum against aluminum chloride (AlCl3)-induced AD in rats by investigating the behavioral, neurochemical, immunohistochemical, and molecular mechanisms that underpin its possible neuroprotective effects. Twenty-four adult albino rats were divided into four groups (n = 6/group): (i) Control (C) received saline per oral (p.o.), (ii) Naringin(N)-received naringin (100 mg/kg/d) p.o, (iii) AlCl3-recived AlCl3 (100 mg/kg/d) p.o and (iv) AlCl3 + Naringin (AlCl3 + N) received both AlCl3 and naringin p.o for 21 days. Behavioral tests showed an increase in the time to reach the platform in Morris water maze, indicating memory impairment in the AlCl3-treated group, but co-administration of naringin showed significant improvement. The Rotarod test demonstrated a decrease in muscle coordination in the AlCl3-treated group, while it was improved in the AlCl3 + N group. Neurochemical analysis of the hippocampus and cerebellum revealed that AlCl3 significantly increased lipid peroxidation and oxidative stress and decreased levels of reduced glutathione. Administration of naringin ameliorated these neurochemical changes via its antioxidant properties. Cerebellar immunohistochemical expression for microtubule assembly (tau protein) and oxidative stress (iNOS) increased in A1C13-treated group. On the other hand, the expression of the autophagic marker (LC3) in the cerebellum showed a marked decline in AlCl3-treated group. Western blot analysis confirmed the cerebellar immunohistochemical findings. Collectively, these findings suggested that naringin could contribute to the combat of oxidative and autophagic stress in the cerebellum of AlCl3-induced AD.